PROBLEMS OF ECONOMIC SECURITY OF UKRAINE AT THE CURRENT STAGE OF ITS DEVELOPMENT - FURDELA, NIKOLETTA; SERZHANOV, VITALIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
This article considers the current problems of economic security of Ukraine. The main threats to the country’s economic security have been identified. It is established that today the most important principle of formation of civilized market relations in Ukraine is to achieve economic security of the state. One of the definitions of this term is: economic security is a state of the national economy that allows to maintain resistance to internal and external threats and is able to meet the needs of the individual, family, society and state. In other words, the economic security of the country is a complex category that characterizes the ability of the national economy to expand self-reproduction in order to ensure the competitiveness of the national economy in the world economic system. Based on the above, it is proved that the provision of national interests and economic security are the most important functions of the state, the implementation of which is designed to strengthen its position in the international community. 303 Unfortunately, today Ukraine does not have a high enough level of economic security. This is due to a number of negative phenomena in the economy and society. One of the most important factors that negatively affects the state of economic security in the country is a phenomenon such as the shadow economy. It is determined that in the common sense, the shadow economy is an economic activity that is not accounted for and not controlled by official government agencies, as well as activities aimed at generating income in violation of applicable law. According to various sources, the level of the shadow economy in Ukraine is about 50% of the country’s real GDP.